The Impact of the Commitment to Pursuing the History of Truth History on the Tour Guide Career Mission - Through the Skill of Oral History - Wang, Ke; Liu, Jin (International Journal of Management and Education in Human Development, 2022)
More and more studies have shown that pursuing historical truth has an important impact on the tourism industry, which is embodied in the professional mission of the tour guide profession, and the historical truth has an important impact on the mission of the tour guide profession. The responsibilities and performance of tour guide work are reflected in the quality of service. The current tourists' demand for tourism services is not only material and information convenience, but they pay more attention to values and spiritual enjoyment. Therefore, tour guides need to provide customers with satisfactory services by teaching reception services and values infection, which will become their professional mission. Oral history is one of the most direct and effective ways for tour guides to existing in the travel industry, and this skill has an important bearing on historical truth. Oral histories, the concept of tour guide missions, and the continuation of human civilization will be important constraints on this argument, and they will be the keys to making this study meaningful.